High‐Strength, Durable All‐Silk Fibroin Hydrogels with Versatile Processability toward Multifunctional Applications. (8th January 2018) - Zhu, Zhenghua; Ling, Shengjie; Yeo, Jingjie; Zhao, Siwei; Tozzi, Lorenzo; Buehler, Markus J.; Omenetto, Fiorenzo; Li, Chunmei; Kaplan, David L.
Abstract: Hydrogels are the focus of extensive research due to their potential use in fields including biomedical, pharmaceutical, biosensors, and cosmetics. However, the general weak mechanical properties of hydrogels limit their utility. Here, pristine silk fibroin (SF) hydrogels with excellent mechanical properties are generated via a binary‐solvent‐induced conformation transition (BSICT) strategy. In this method, the conformational transition of SF is regulated by moderate binary solvent diffusion and SF/solvent interactions. β‐sheet formation serves as the physical crosslinks that connect disparate protein chains to form continuous 3D hydrogel networks, avoiding complex chemical and/or physical treatments. The Young's modulus of these new BSICT–SF hydrogels can reach up to 6.5 ± 0.2 MPa, tens to hundreds of times higher than that of conventional hydrogels (0.01–0.1 MPa). These new materials fill the "empty soft materials' space" in the elastic modulus/strain Ashby plot. More remarkably, the BSICT–SF hydrogels can be processed into different constructions through different polymer and/or metal‐based processing techniques, such as molding, laser cutting, and machining. Thus, these new hydrogel systems exhibit potential utility in many biomedical and engineering fields. Abstract : Pristine silk fibroin hydrogels with high strength and toughness are prepared by a binary‐solvent‐induced conformation transition strategy. The formation of a β‐sheet serves as the physical crosslinks that connect disparate protein chains to form continuous 3D hydrogel networks. Furthermore, versatile processing techniques are used to generate functional hydrogel constructs of complex features.